GAMBARAN SELF ESTEEM PADA ANAK SEKOLAH MENENGAH PERTAMA SEBAGAI UPAYA PENCEGAHAN BULLYING DI SMP NEGERI 15 KOTA BENGKULU - Lestari, Puja; Aprilatutini, Titin; Sardaniah, Sardaniah; Sorena, Esti; Yustisia, Nova (Fakultas Ilmu Kesehatan Universitas Muhammadiyah Bengkulu, 2023)
A person's opinion of their ability to sustain whatever they want, expressed as agreement or disagreement with their attitudes and beliefs that they are capable, significant, successful, and valued, is known as self esteem. To be able to support self-actualization, the ultimate desire in human life, one must have self esteem. Bullying produces a range of negative physical, psychological and emotional effects, including mental distress, psychological trauma, fear, insecurity and resentment. It also decreases students' learning motivation, concentration, creativity, initiative, and (mental) endurance. The purpose of this study was to determine the description of self esteem in junior high school children as an effort to prevent bullying at SMP Negeri 15 Bengkulu City. This research is quantitative descriptive research. The study population was 291 people, the sample taken was 74 people with stratified random sampling used as a sampling method, and a questionnaire. The instrument used in this study was a questionnaire sheet describing self esteem using the Rosenberg Self Esteem Questionnaire (RSES). The results of this study indicate that most students and female students have high self esteem, namely 54 respondents with a percentage of 73%, while low self esteem is 20 respondents with a percentage of 27%. Most of the respondents are in the high self esteem category. Children who have positive thinking, feel valuable, meaningful, and helpful are children who seek fulfillment or strong self-esteem, so they do not oppress others, and can stop oppressing themselves.